Answers

2015-11-05T20:15:17+05:30
1). I = nE/R + nr
⇒ I= n(E/R + r)
⇒ n = I / (E/R + r)

2).
I = nE/R + nr
⇒ I - nE/R = nr
⇒ (I - nE/R)/n = r
⇒ I/n - E/R = r or r = I/n - E/R
2 3 2
Hope it helps :) and if it does please click on thanks button above & mark as best answer ^_^
check 1st soln it should be n = I/(ER+r)
2015-11-05T20:20:21+05:30
1) I=nE /R+nr--->I=n (E/R+r)--->I=n (E +rR /R)-->n =IR /E +rR 2)I=nE /nR +r-->I=nE +nRr /nR --->I=n (E +Rr) /nR here N gets cancelled then I=E +Rr /R-->Rr =IR -E--->r =IR-E /R.
1 2 1